Concert Viewing Headphones. (7th February 2012) - Atsuta, Kazuya; Hamanaka, Masatoshi; Lee, SeungHee
Abstract : An audiovisual interface equipped with a projector, an inclina-tion sensor, and a distance sensor for zoom control has been developed that enables a user to selectively view and listen to specific performers in a video-taped group performance. Dubbed Concert Viewing Headphones, it has both image and sound processing functions. The image processing extracts the portion of the image indicated by the user and projects it free of distortion on the front and side walls. The sound processing creates imaginary microphones for those performers without one so that the user can hear the sound from any performer. Testing using images and sounds captured using a fisheye-lens camera and 37 lavalier microphones showed that sound locali-zation was fastest when an inverse square function was used for the sound mixing and that the zoom function was useful for locating the desired sound performance.